Enteral stents in the management of gastrointestinal leaks, perforations and fistulae - Hany Shehab; Todd H. Baron (Gastrointestinal Intervention, 2016)
Gastrointestinal leaks and fistulae are grave conditions associated with substantial morbidity and mortality. Expandable stents have shown significant success in the management of leaks and fistulae, providing an efficacious minimally invasive approach in patients who are frequently poor surgical candidates. Most reports, however, are limited by their small size or the pooling of different stents, techniques and locations of leaks and fistulae. Despite the numerous alterations in stent design, migration remains the pivotal drawback of this technique. In this article, we review the current status of expandable stents in the management of gastrointestinal leaks and fistulae, available anti-migration techniques and evolving innovations in stent design.